2020
DOI: 10.1007/s11356-020-09990-9
|View full text |Cite
|
Sign up to set email alerts
|

Multi-route human health risk assessment from trihalomethanes in drinking and non-drinking water in Abadan, Iran

Abstract: Natural organic matter reacted with chlorine used for disinfection, and finally, trihalomethanes (THMs) are formatted. The main purpose of this study was to determine four THM concentrations and human health cancer risk and non-cancer risk assessment from exposure through oral ingestion, dermal contact, and inhalation for males and females in Abadan. Two sampling sites were selected, and five samples before and after treatment by two different water treatment systems (RO and ion exchange) were collected every … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
3
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 23 publications
3
22
3
2
Order By: Relevance
“…They observed similar patterns in the incremental increases of CDIs as well as HIs and cancer risk for up to 9 showering events, exponential increase in the beginning, and slower rate towards the 9th event. Generally, in the studies, the HI of inhalation is left unattended either because the inhalation-CDI is less than ingestion and dermal CDIs or because of the lack of RfD values for inhalation risk (Kujlu et al, 2020;Kumari and Gupta, 2018;Mosaferi et al, 2021). However, assessing the inhalation-HI along with the other two gives a clear idea about how much it differs from them and can be used in future studies for inclusion in the database.…”
Section: Total Hazard Index Through Successive Showersmentioning
confidence: 99%
See 1 more Smart Citation
“…They observed similar patterns in the incremental increases of CDIs as well as HIs and cancer risk for up to 9 showering events, exponential increase in the beginning, and slower rate towards the 9th event. Generally, in the studies, the HI of inhalation is left unattended either because the inhalation-CDI is less than ingestion and dermal CDIs or because of the lack of RfD values for inhalation risk (Kujlu et al, 2020;Kumari and Gupta, 2018;Mosaferi et al, 2021). However, assessing the inhalation-HI along with the other two gives a clear idea about how much it differs from them and can be used in future studies for inclusion in the database.…”
Section: Total Hazard Index Through Successive Showersmentioning
confidence: 99%
“…For instance, dishwashing eliminates dermal absorption that can occur during the hand washing of utensils. A common assumption in the inhalation CDI assessment is that the shower room air is considered free of THMs before any showering events (initial THM concentration = 0) (Chowdhury, 2013; Kujlu et al, 2020). This assumption is correct only for the household shower rooms where members use separate bathrooms or there is enough time between successive showering events so that the THM concentration left by the previous user is subsided.…”
Section: Introductionmentioning
confidence: 99%
“…After continuous improvement by the U.S. EPA and other agencies, the four-step evaluation method has developed into a human health risk assessment model (HHRA) (US National Research Council, 1983), which has been widely accepted. It has been used to evaluate the human health risks of drinking water (Pérez et al, 2019;Kujlu et al, 2020), surface water (Zhang et al, 2015;Zhu et al, 2015;Li et al, 2020), groundwater (Edokpayi et al, 2018;, and polluted water by a large number of researchers. Zhao et al (2020) found that the human health risk through drinking water is two to three orders of magnitude greater than that of skin contact after the risk analysis of heavy metal pollution in the surface water of the Three Gorge Reservoir.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, dishwashing eliminates dermal absorption that can occur during the hand washing of utensils. A common assumption in the inhalation CDI assessment is that the shower room air is considered free of THMs before any showering events (initial THM concentration = 0) (Chowdhury, 2013; Kujlu et al, 2020). This assumption is correct only for the household shower rooms where members use separate bathrooms or there is enough time between successive showering events so that the THM concentration left by the previous user is subsided.…”
Section: Introductionmentioning
confidence: 99%